2013
DOI: 10.3758/s13423-013-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

Belief bias during reasoning among religious believers and skeptics

Abstract: We provide evidence that religious skeptics, as compared to believers, are both more reflective and effective in logical reasoning tasks. While recent studies have reported a negative association between an analytic cognitive style and religiosity, they focused exclusively on accuracy, making it difficult to specify potential underlying cognitive mechanisms. The present study extends the previous research by assessing both performance and response times on quintessential logical reasoning problems (syllogisms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 32 publications
(50 reference statements)
4
60
0
1
Order By: Relevance
“…Moreover, across these studies, this relation holds even after controlling for age, sex, ethnicity, socioeconomic status, income, year in university, university faculty, education (in a non-university sample), political ideology, various personality variables, moral values, and cognitive ability (Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook et al, 2012;; but see also Razmyar & Reeve, 2013). Religious skeptics also spend more time on reasoning tasks than believers (Pennycook, Cheyne, Koehler, et al, 2013;Pennycook 2014). Finally, experimental evidence indicates that subtle manipulations of intuitive versus reflective thinking modes are sufficient to decrease religious belief .…”
Section: Toward a Cognitive Mechanistic Account Of Individual Religionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, across these studies, this relation holds even after controlling for age, sex, ethnicity, socioeconomic status, income, year in university, university faculty, education (in a non-university sample), political ideology, various personality variables, moral values, and cognitive ability (Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook et al, 2012;; but see also Razmyar & Reeve, 2013). Religious skeptics also spend more time on reasoning tasks than believers (Pennycook, Cheyne, Koehler, et al, 2013;Pennycook 2014). Finally, experimental evidence indicates that subtle manipulations of intuitive versus reflective thinking modes are sufficient to decrease religious belief .…”
Section: Toward a Cognitive Mechanistic Account Of Individual Religionmentioning
confidence: 90%
“…There is some evidence for this claim, although it should be noted that the research discussed below is in its infancy and, as a *Email: gpennyco@uwaterloo.ca Religion,Brain & Behavior 247 consequence, the findings cannot be generalized outside of Western, predominantly Christian societies. A growing body of research indicates that people who are more willing to engage analytic reasoning when confronted with problems that contain intuitive lures are less likely to hold supernatural religious beliefs Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014a, 2014bPennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook, Cheyne, Seli, Koehler, & Fugelsang, 2012;; for a review, see Pennycook, 2014). Moreover, across these studies, this relation holds even after controlling for age, sex, ethnicity, socioeconomic status, income, year in university, university faculty, education (in a non-university sample), political ideology, various personality variables, moral values, and cognitive ability (Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook et al, 2012;; but see also Razmyar & Reeve, 2013).…”
Section: Toward a Cognitive Mechanistic Account Of Individual Religionmentioning
confidence: 99%
“…Following the pioneering work of Stanovich and colleagues (Stanovich & West, 1998, 2000, see Stanovich, 2004, 2009a, 2009b for reviews), much recent research has been focused on the consequences of such individual differences using tasks such as the CRT. Several studies have demonstrated that analytic cognitive style is predictive in a number of domains that are widely considered psychologically important, such as moral judgments (Paxton, Unger, & Greene, 2012;Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014a), moral values (Pennycook et al, 2014a;Rozyman, Landy, & Goodwin, 2014), creativity (Barr, Pennycook, Stolz, & Fugelsang, 2014) and, crucially for present purposes, religiosity (Gervais & Norenzayan, 2012;Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014b;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook et al, 2012;Shenhav et al, 2012; see Pennycook, 2014 for a review).…”
Section: Analytic Cognitive Stylementioning
confidence: 99%
“…Stanovich (e.g., 2004;2009b) has argued that thinking disposition is an underappreciated determinant of psychological outcomes. Recent research has supported the idea that cognitive style plays a consequential role in psychological domains that are of some general import (Pennycook, Fugelsang, & Koehler, 2015b): e.g., creativity (Barr, Pennycook, Stolz, & Fugelsang, 2014), moral judgments and values (Paxton, Unger, & Greene, 2012;Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014b;Rozyman, Landy, & Goodwin, 2014), religious belief (Gervais & Norenzayan, 2012;Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook, Ross, Koehler, & Fugelsang, 2016;Shenhav, Rand, & Greene, 2012), bullshit receptivity (Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2015), and even Smartphone technology use (Barr, Pennycook, Stolz, & Fugelsang, 2015 …”
Section: Individual Differences In Analytic Thinkingmentioning
confidence: 99%